The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fgene.2023.976051
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes and preferences about expanded noninvasive prenatal testing

Abstract: Introduction: Noninvasive prenatal testing (NIPT) using cell-free DNA (cfDNA) is typically carried out to screen for common fetal chromosomal anomalies, with the option to screen for a wider range of chromosomal changes (expanded NIPT) becoming increasingly available. However, little is known about pregnant patients’ attitudes and preferences regarding expanded NIPT.Methods: To address this gap, we surveyed general-risk patients having first-tier cfDNA screening at a private prenatal clinic on their expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…This is complemented by the cost-utility analysis performed by Anh et al, indicating NIPT as a cost-effective alternative for high-risk pregnant women in Vietnam, presenting a strong case for the broader adoption and insurance coverage of NIPT in developing countries (19,31). The diagnostic preferences indicated by our study participants show a growing acceptance of NIPT over invasive methods such as amniocentesis, signaling a shift toward patient-centric benefits (32,33).…”
Section: Discussionsupporting
confidence: 63%
“…This is complemented by the cost-utility analysis performed by Anh et al, indicating NIPT as a cost-effective alternative for high-risk pregnant women in Vietnam, presenting a strong case for the broader adoption and insurance coverage of NIPT in developing countries (19,31). The diagnostic preferences indicated by our study participants show a growing acceptance of NIPT over invasive methods such as amniocentesis, signaling a shift toward patient-centric benefits (32,33).…”
Section: Discussionsupporting
confidence: 63%
“…However, currently there is no consensus on which other variants should be included in NIPT, and professional societies are warning that caution should be exercised [42,43]. Studies have shown that most pregnant couples would prefer to learn more information about their unborn child [44,45], even to the point of accepting a less accurate test in exchange for receiving this information [46]. Nevertheless, the potential benefits and harms of these expanded tests need to be evaluated, preferably in advance of their introduction into clinical practice [47].…”
Section: Challenges In Prenatal Screening: Ensuring Informed and Auto...mentioning
confidence: 99%